Migration and identity of Cape Verdeans and their descendants in Argentina - Maffia, Marta Mercedes (2010)
The paper will focus on the Cape Verdean diaspora in Argentina since their arrival at the end of the nineteenth century; emphasizing their distinctive demographic characteristics, places of settlement, development of popular organizations as well as the specific identity strategy they devised in dealing with the invisibleness and the ‘‘Argentinization’’ process imposed upon them. The paper also examines the construction of a diaspora conscience and the ways in which African cultural elements were incorporated by the second and third generations in the making of the Cape Verdean diaspora in Argentina.